2013
DOI: 10.1136/annrheumdis-2013-203566
|View full text |Cite
|
Sign up to set email alerts
|

An immunological biomarker to predict MTX response in early RA

Abstract: Baseline T-cell subset analysis has a value in predicting early RA remission with first therapy with MTX. Immunological analysis could be used in conjunction with clinical/serological features to predict response to MTX and help select the most appropriate therapy at disease presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 32 publications
3
45
1
3
Order By: Relevance
“…Defining Tregs based on only CD4 + CD25 +/high without the use of CD127 or FOXP3 markers may account for some of the conflicting results [50]. A recent study showed that frequencies of Tregs (defined based on FOXP3 expression) are lower in patients with ueRA than in HCs [51]. On the contrary, we saw an increased frequency (based on FOXP3 expression) or similar frequency (based on CD25 + CD127 low expression) of circulatory Tregs in patients with ueRA compared with that in HCs.…”
Section: Discussionmentioning
confidence: 97%
“…Defining Tregs based on only CD4 + CD25 +/high without the use of CD127 or FOXP3 markers may account for some of the conflicting results [50]. A recent study showed that frequencies of Tregs (defined based on FOXP3 expression) are lower in patients with ueRA than in HCs [51]. On the contrary, we saw an increased frequency (based on FOXP3 expression) or similar frequency (based on CD25 + CD127 low expression) of circulatory Tregs in patients with ueRA compared with that in HCs.…”
Section: Discussionmentioning
confidence: 97%
“…What directs this process to the joints is unknown and it probably includes biomechanical factors, neuro-immuno-endocrinological interactions and altered articular microvascular microenvironment. Several factors have been proposed to have an association with the susceptibility and severity of rheumatoid arthritis [1][2][3][4][5][6][7][8][9][10].…”
Section: What Is the Origin Of This Complex Cytokine Response?mentioning
confidence: 99%
“…While we do this, we are generally treat the "normal and abnormal cytokine response" at the same time, because we do not know the main etiology of this abnormal cytokine response. To beter manage RA, we should understand the role of cytokines and the relation between the efector cells [1][2][3][4][5][6].…”
Section: Cytokine and Rheumatoid Arthritismentioning
confidence: 99%
“…Conflicting non-statistically significant associations between age and response were found (Figure 1a). [1][2][3][4] Female gender was found to be a predictor of non-response in two studies (OR (odds ratio) 0.55 and 0.54), but these findings could not be replicated in two other studies (Figure 1b). [1][2][3][4] In two studies, smoking predicted non-response (adjusted OR 0.35 and 0.60), but this was inconsistent over all response criteria assessed (Figure 1c).…”
mentioning
confidence: 99%